Drug Interaction in Psycho-Oncology: Antidepressants and Antineoplastics - Miguel, C (2011)
Background and Objectives: Although there is a growing impact of psychiatric and depressive disorders in cancer patients, literature on the idiosyncrasies of antidepressants (ADs) used in those conditions and their interactions with antineoplastic agents (ANs) is scarce. Sharing the same biotransformation pathways enhances the risk of drug interaction between ADs and ANs, specifically when compounds are inducers, inhibitors or substrates of cytochrome P450 (CYP 450). In cancer patients, such drug interactions may result in less efficacy of the drug and/or increase of their side effects. Therefore, the choice of AD should be cautious (safe and effective) and well supported. The main purpose of this review was to analyze the individual pharmacokinetic properties of the most used ADs and ANs in order to summarize the risk of possible drug interactions between them, anticipating the consequences of their coadministration. Methods: The authors reviewed books and PubMed online articles published in the last 6 years. Results: Most of the ANs are subject to transformation by CYP 450 3A4 and their coadministration with ADs, that have inhibitory properties of this CYP isoform, such as fluoxetine, sertraline, paroxetine and fluvoxamine, may result in the loss of the AN's efficacy or higher toxicity. Conclusion: Among the ADs, escitalopram, citalopram, venlafaxine, mirtazapine and milnacipran stand out for their weak CYP 450 inhibitory potential and their safety profile in those patients.